Pemberdayaan Budikdamber Sebagai Upaya Pemulihan Ekonomi Masa Pandemi di Wilayah Sekaran Gunung Pati - Hagai Kuncoro; Karnawati Karnawati (Jurnal Teologi Berita Hidup, 2021)
The pandemic has caused an economic downturn in the Sekaran Gunung Pati area, Semarang. The Banaran Community Center as a Christian institution seeks to internalize the attitude of Jesus who cares for people who suffer and need help, has facilitated by providing empowerment in the form of catfish farming in buckets (budikdamber). The method of implementation is through the stages of preparation, assessment, program planning, formulation of action plans, program implementation, evaluation and termination. The results of the budikdamber show that the assisted groups experience additional insight into catfish cultivation in buckets, an increase in the economy in the family and gain insight into effective marketing strategies. This paper contributes to the context of a mission strategy through community empowerment.Pandemik menyebabkan kelesuan ekonomi di wilayah Sekaran Gunung Pati Semarang. Pusat Komunitas Banaran selaku Lembaga kristen berupaya menginternalisasi sikap Yesus yang peduli kepada orang-orang yang menderita dan membutuhkan pertolongan, telah menfasilitasi dengan memberikan pemberdayaan berupa budidaya ikan lele dalam ember (budikdamber). Metode pelaksanaan melalui tahapan persiapan, pengkajian, perencanaan program, formulasi rencana aksi, implementasi program, evaluasi dan terminasi. Hasil budikdamber didapati bahwa kelompok dampingan mengalami penambahan wawasan dalam budidaya lele dalam ember, adanya peningkatan ekonomi dalam keluarga dan bertambahnya wawasan dalam strategi pemasaran yang efektif. Tulisan ini memberi kontribusi dalam konteks strategi misi melalui pemberdayaan masyarakat.